1997
DOI: 10.1111/j.1432-1033.1997.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of the Cell‐Envelope Oligosaccharide from the Lipopolysaccharide of Haemophilus Influenzae Strain RM.118‐28

Abstract: The structure of the oligosaccharide part of the Haemophilus influenzue RM.118-28 lipopolysaccharide (LPS) has been investigated. The oligosaccharide was obtained from the LPS by mild acid hydrolysis followed by gel-permeation chromatography, and was studied by methylation analysis, NMR spectroscopy and mass spectrometry. The structure of the major compound, which is a hexasaccharide, is proposed as follows.PIn the structure, Kdo is 3-deoxy-~-manno-octu~osonic acid, PEtn is phosphoethanolamine, PCho is phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
61
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 20 publications
7
61
0
1
Order By: Relevance
“…zae phosphocholine was also identified on the surface and was found to be attached to the lipopolysaccharide (18,19). All bacteria having phosphocholine as part of their surface structures colonize the human nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
“…zae phosphocholine was also identified on the surface and was found to be attached to the lipopolysaccharide (18,19). All bacteria having phosphocholine as part of their surface structures colonize the human nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of H. influenzae LPS have demonstrated that PCho can be linked to hexoses attached to any one of the three heptoses (19,25,27). Lysenko and colleagues have shown that the lic1D gene directs this addition and that the location of the PCho molecule can alter the susceptibility of the bacteria to CRP-mediated bacterial killing (17).…”
mentioning
confidence: 99%
“…Modification of the LPS by addition of two PCho residues resulted in increased binding of C-reactive protein and had consequential effects on the resistance of the organism to the killing effects of normal human serum compared to the effects of glycoforms containing one or no PCho. When bound, C-reactive protein leads to complement-mediated killing, indicating the potential biological significance of multiple PCho residues.Phosphocholine (PCho) has been detected on the cell surface of a range of bacteria, predominantly bacteria residing in the human respiratory tract, such as Haemophilus influenzae (5,25,39). In H. influenzae, PCho is a substituent of the lipopolysaccharide (LPS) molecule (24,25,39), the main glycolipid on the bacterial cell surface that is a target for host immune responses and influences both the commensal and pathogenic behavior of the organism (38).…”
mentioning
confidence: 99%
See 2 more Smart Citations